RUSSIAN IN THE MULTIETHNIC REGION (ON MATERIAL OF COMPOSITIONS BY YA. M. NEVEROV, DIRECTOR OF STAVROPOL PROVINCIAL GYMNASIUM 1850–1860) - K. E. Stain; D. I. Petrenko (Гуманитарные и юридические исследования)
The article is devoted to consideration of the activity concept of training in Stavropol provincial gymnasium under the leadership of a philosopher, a teacher, and a literary critic Ya.M. Neverov. He developed an educational model which is applicable nowadays in the multinational region of the Caucasus. What is now defined as peace-making through the dialogue of cultures and by means of languages, literature and arts, was put into practice in the gymnasium in the middle of the XIX century by Ya.M. Neverov.